Effect of different ligands on the controlled polymerization of monodisperse polystyrene nanospheres by atom transfer radical polymerization in an aqueous emulsion - E. J. Tang; M. Yuan; B. Y. Tian; S. J. Liu; P. J. Hu; X. Y. Zhao; D. S. Zhao (eXPRESS Polymer Letters, 2012)
Polystyrene nanospheres have been synthesized by atom transfer radical polymerization (ATRP) to control the molecular weight distribution in the aqueous system. The crucial factor in such a system is the ligand that adjusts the solubility of the catalyst in different phases to control the concentration of both the activator and the deactivator in reaction phase. The effect of different ligands including ethylenediamine, 1,10-phenanthroline (phen) and 4,4-dinonyl-2, 2-bipyridyl (dNbpy) on the catalytic solubility in the organic and aqueous phase has been investigated. The molecular weight distribution of polymer obtained in this way was analyzed by gel permeation chromatography (GPC). It showed that the obtained polymer particles presented a broad molecular weight distribution (polydispersity index 1.78) with ethylenediamine as the ligand, but the polymerization rate was high and conversion reached 96.8%. The molecular weight distribution of polystyrene was narrowest with dNbpy as ligand, but the conversion was lowest and only achieved to 69%. Possible reasons were the influence of the structure of three different ligands on the control of ATRP reaction. SEM and GPC indicated that the polystyrene nanospheres presented regular sphere with a diameter of about 120 nm and uniform molecular weight distribution, which possessed a significant potentials in drug carrier field.